One Actor, Multiple Roles: The Performances of Cryptochrome in Drosophila - Damulewicz, Milena; Mazzotta, Gabriella M. (Frontiers in Physiology, 2020)
Cryptochromes (CRYs) are flavoproteins that are sensitive to blue light, first identified in Arabidopsis and then in Drosophila and mice. They are evolutionary conserved and play fundamental roles in the circadian clock of living organisms, enabling them to adapt to the daily 24 h cycles. The role of CRYs in circadian clocks differs among different species: in plants they have a blue light sensing activity whereas in mammals they act as light-independent transcriptional repressors within the circadian clock. These two different functions are accomplished by two principal types of CRYs, the light-sensitive plant/insect type 1 CRY, and the mammalian type 2 CRY acting as negative autoregulator in the molecular circadian clockwork. Drosophila melanogaster possesses just one CRY, belonging to type 1 CRYs. Nevertheless, this single CRY appears to have different functions, specific to different organs, tissues and even subset of cells in which it is expressed. In this review we will dissect the multiple roles of this single CRY in Drosophila, focusing on the regulatory mechanisms that make its pleiotropy possible.